Profil personaliti pelajar-pelajar program matrikulasi Universiti Putra Malaysia - Mohd Noah, Sidek; Jailani, Othman (Universiti Putra Malaysia Press, 2002)
This descriptive study was conducted to determine the pattern of personality profile amongst the students of matriculation programs in Universiti Putra Malaysia, Serdang, Selangor. This study also aimed to determine whether there were any differences in personality between male and female students according to specialization areas. The subjects of this study were 340 students who were selected using the stratified random sampling from a total of 1475 students of Science, Engineering, Medical, Accounting and TESL matriculation programs. The instrument used in this study was the Sidek Personality Inventory (IPS). The data obtained were then analysed using the descriptive statistic including the mean, standard deviation and frequency. The finding of this study was that each specialization area has shown the same personality pattern. The finding clearly indicated that some major traits of personality which were identified as the ideal personality for the student in higher education such as analytical, intellectual, and endurance traits were only at the medium level whereas for the dependent and self-critical traits, it was quite high. The finding also indicated that there were no significant differences in personality traits based on specialization area and gender of the students. Pertaining to the research findings, several implications and recommendations were put forward.